Job Satisfaction’s Role in Mediating the Influence of Workload and Work Culture on Employee Performance of Community Health Center at Klungkung - Trisnayani, Ketut; Gunadi, I Gusti Ngurah Bagus; Landra, Nengah; Putra, I Gede Cahyadi (Asia Pacific Journal of Management and Education (APJME), 2024)
Community health center is a community that has a vital role in the growth of human resources. If health services are low, it will greatly affect all sectors of community growth, including the economy in the area. The aim of this research is to determine and analyze the influence of psychological workload and work culture on performance with job satisfaction as a mediator. The population is all employees of the UPTD Puskesmas Banjarangkan I Klungkung with total of 78 people. The analysis technique used is SEM–PLS. The research results show that psychological workload has no significant effect on employee performance, work culture has a significant effect on employee performance, job satisfaction has a significant effect on employee performance, psychological workload has no significant effect on job satisfaction, and work culture has a significant effect on job satisfaction. The implication of this research is that community health centers must continue to improve the performance and satisfaction of their employees so that employees can provide excellent service to the community.